“Título: Antecedentes Gíneco-optétrico de la vagino-sis en gestantes en el hospital I IPSS Moyobamba periodo mayo – 1994 abril 1995” - Soria Vargas, ·Hazel .Eunice (1995)
This is a descriptive, accomplished in Moyobamba, in order to study applied with the Hospital's support I IPSS level determine the background ginecoobstetricas associated with vaginosis in pregnant women. The vaginosis bacterial is the infection more often of the female in the stage reproductive; It's a disease process that affects the vagina, but characteristically not presenting injury or inflammation, considered as a syndrome that results from a series of alterations in the aerobic and anaerobic bacterial flora, which translates into physical and chemical changes of vaginal secretions and involving the characteristics of the host and the sexual partner. Our population was comprised of 200 patients in which took samples of vaginal discharge and was carried out examination of Gram, Graham, Pap smear and culture. The frequency of vaginosis was 86.5 per cent; those factors associated were home of relationships sex to those 15 to 18 years and pr...